Evaluation of mechanical properties of dissimilar aluminium alloys during friction stir welding using tapered tool. Issue 1 (1st January 2021) - Attah, Benjamin I.; Lawal, Sunday A.; Akinlabi, Esther T; Bala, Katsina C.
Abstract: This study examined the effect of AISI H13 steel-tapered tool on the dissimilar friction stir welding of 7075-T651 and 1200-H19 aluminium alloys. Three mechanical tests which include hardness, tensile strength and impact energy were conducted to study the effect of tilt angle, rotational and welding speeds on the weld integrities, 50 and 175 HV were respectively obtained as hardness values for AA1200- H19 and AA 7075- T651, the hardness values were measured for three selected welding speeds of 30, 60 and 90 mm/min representing low, medium and high at a constant rotational speed of 1500 rpm, a tool tilt angle of 2°.The hardness increases with the welding speed from 81.99 to 98.5 HV as the speed increased from 30 to 60 mm/min and dropped to 77 HV at 90 mm/min.The impact energy increased from 12.9 to 21.4 J with an increase in the welding speed from 30 to 60 mm/min and dropped to 5.4 J at 90 mm/min.The ultimate tensile strength (UTS) increased from 126.04 to 151.54 MPa with an increase in the welding speed from 30–60 mm/min and decreased from 151.54 to 128.37 MPa, the hardness at 1500 rpm and 60 mm/min increased from 70.22 to 98.58 HV with an increase in the tilt angle from 1- 2 ° , a further increase from 2–3 o reduced the hardness from 98.58 to 66 HV, UTS increased from 123.32 to 151.54 MPa as tilt angle increased from 1–2 ° and decreased to 122.2 MPa, the medium tilt angle of 2 ° , rotational and traverse speeds of 1500 rpm and 60 mm/min respectively gave the highest impact energy of 21.4 J.